Multivariate analysis of prognosis of patients with malignant bowel obstruction - CHENG Wei, HUANG Yuhua, WANG Jian, LI Yousheng (Waike lilun yu shijian, 2022)
Objective To analyze the risk factors for prognosis of patients with malignant bowel obstruction (MBO) using multiple factors, and establish the nomogram model for predicting the survival of patients with MBO. Methods The clinical data of 203 patients with MBO from June 2013 to June 2019 who were followed up in our hospital were analyzed retrospectively. Results A total of 143 (70.4%) patients have been followed up. It was shown with univariate analysis that indexes of gender, age, platelet, C-reactive protein, and total protein levels, comorbidities, the treatment with somatostatin, enteral nutrition, and parenteral nutrition, length of hospital were not related to the survival of patients with MBO. There were some factors including late TNM stage of tumor (P<0.001), tumor metastasis (P<0.001), anemia (P=0.001), lower albumin (P<0.001), higher white blood cell(P=0.023), non-surgical treatment(P=0.013), low quality of life score (P<0.001) and poor liver function [including high alanine aminotransferase (P=0.023), high aspartate aminotransferase (P=0.005)] which related with poorer prognosis in patients with MBO. Multivariate analysis showed that tumor stage (P=0.003) and albumin level(P=0.001) were independent risk factors affecting the prognosis of MBO. Nomogram was constructed using 4 indexes including late TNM stage, tumor metastasis, lower hemoglobin and lower albumin. It was indicated that the results of internal prognosis were better for the prediction of survival of 3 to 12 months of 40 cases. Conclusions The study on poor prognosis of patients with MBO combined with nomogram showed that both late stage of tumor and malnutrition were main factors.